Analisis Pendapatan, Biaya Bersumber Underwriting, dan Sumber Investasi Lain pada Perusahaan Asuransi Kerugian - Yohanes Jhony Kurniawan; Heppy Julianto (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This research aims to create a general map of Income, Costs Sourced from Underwriting and Other Investment Sources in Casualty Insurance Companies. So based on the above we will raise the research title "Analysis of Income, Costs Sourced from Underwriting and Other Investment Sources in Casualty Insurance Companies in 2018 - 2022." This research aims: To find out the income of the casualty insurance industry in Indonesia, to find out the industry's income Loss insurance in Indonesia comes from underwriting or other investment sources, to find out the costs of the loss insurance industry in Indonesia, and to find out the costs of the loss insurance industry in Indonesia from underwriting or other investment sources. This research method is quantitative descriptive. 1. The conclusion is that the income of the loss insurance industry in Indonesia from 2018 to 2022 tends to increase from 2018 to 2019, 2020 and 2022, while in 2021 it tends to decrease. Income from the Loss Insurance Industry from Underwriting Sources and from other Investment Sources, during 2018 to 2022 shows a positive upward trend from 2018, 2019, 2021 and 2022, but shows a decreasing trend in 2020. Slightly different from Underwriting Results, the percentage increases in 2020. 2018 to 2019, decreasing in 2020, 2021, and decreasing in 2021. The average for five years is 78%, with a positive trend. Meanwhile, in Figure 3.3, the percentage of Investment Return income shows an increase from 2018 to 2019, 2022 and a decrease in 2020, 2021. The average for five years is 22% with a slight downward trend. Total Underwriting Expenses experienced an upward or positive trend from 2018, 2019, 2020, and 2022, while experiencing a downward or negative trend in 2021. This is also consistent with the Underwriting Costs of the Casualty Insurance Industry for 2018 - 2022, in percentage terms, respectively. also experienced an upward or positive trend from 2018, 2019, 2020, and 2022, while experiencing a downward or negative trend in 2021. Underwriting Costs for the Loss Insurance Industry in 2018 – 2022, In millions of rupiah it can be concluded that in general the amount of operating expenses tends to increased, from 2018 to 2022, only in 2021 did it decrease, and the results of other expenses tended to be stable.